Shakedown solutions for pavements with materials following associated and non-associated plastic flow rules - Liu, Shu; Wang, Juan; Yu, Hai-Sui; Wanatowski, Dariusz (Elsevier, 2016)
Existing lower-bound shakedown solutions for pavement problems are generally obtained by assuming that materials obey an associated flow rule, whereas plasticity of real materials is more inclined to a non-associated flow. In this paper, a numerical step-by-step approach is developed to estimate shakedown limits of pavements with Mohr–Coulomb materials. In particular, influences of a non-associated flow rule on the shakedown limits are examined by varying material dilation angle in the numerical calculations. It is found that the decrease of dilation angle will lead to accelerated reduction of pavement shakedown limits, and the reduction is most significant when the material friction angle is high. Furthermore, existing lower-bound shakedown solutions for pavements are extended, in an approximate manner, to account for the change of material dilation angle and the shakedown results obtained in this way agree well with those obtained through the numerical step-by-step approach. An example of pavement design using shakedown theory is also presented.